Cryptocurrency Investment Mechanism With Bitcoin Instruments in Indonesia - Muhammad Ikbalul Kirom (NAROTAMA UNIVERSITY, Indonesia, 2022)
Cryptocurrency is a digital trading market that offers a new investment instrument in the midst of the investment polemic in the era of the virtual economy. Bitcoin was one of the first tokens in the cryptocurrency market that became a reference for other tokens in the cryptocurrency market. Bitcoin was created by a group that calls itself Satoshi Nakamoto in 2009. The purpose of bitcoin was created as a currency protection asset from the destruction of inflation and a currency replacement tool when the world economy is weakening. Now bitcoin as one of the world's investment instruments has been in great demand by the public, both individuals, institutions, and countries.